Transterradas : child and youth exile as a place of memory - González de Oleaga, Marisa; Meloni González, Carolina, 1975-; Saiegh Dorín, Carola, 1968- (Emerald Publishing Limited : Information Age Publishing, Inc., 2023)
"This book provides a set of testimonies that bring into focus the children and adolescents who have been driven from their lands as subjects with rights who have different ways of envisioning the world. For that reason, this book may be of interest to those experiencing childhood or adolescence in this way; similarly, it may offer insight for those who-for professional or family reasons-are in touch with these young people, including teachers, psychologists, parents, classmates and teens, counselors, social workers and others. Yet within these pages, the landscapes we sketch are also, in some sense, reflections of past atmospheres. And for this reason, historians, sociologists, anthropologists, and other scholars will also find material for academic investigation herein. As values and beliefs come into play in this book, it can inform perspectives on ethics or political philosophy as well. The relationship with others, the behaviors unique to children and adolescents-and the corresponding social sanctions of these behaviors-and the relationship between public and private during this period of life could be other areas to explore. Like the indecipherable Swiss army knife, the genre of this book is difficult to pinpoint. It is an essay but also a piece of literature and the discerning reader will also find historiographical, philosophical, and political reflections in these pages. One more book. Another book. Books are almost always an adventure and what is written therein is, like a map, only part of the journey. An important part, no doubt, but still merely a part. Experience-the true challenge-is up to the reader"-- Provided by publisher.
Translation of: Transterradas : el exilio infantil y juvenil como lugar de memoria.
Keywords: Exiles' writings, Argentine.; Exiles -- Argentina -- History -- 20th century.; Refugee children -- Argentina.; Argentina -- History -- Dirty War, 1976-1983 -- Personal narratives.; elektronické knihy; Personal narratives.; Social Science -- Children's Studies.; Moral and social purpose of education.; Age groups: children.; electronic books